Implementation of The Fulfullment of The Rights of Migrant Workers Post Plecement in Pamekasan, Indonesia - Devi Rahayu,; Mishbahul Munir,; Dwi Nuril Latifah, (Technium Social Sciences Journal, 2023)
Everyone who works abroad to fulfill their economic needs is a migrant worker. Migrant workers are Indonesians whose goal is to seek sustenance abroad to fulfill their needs. Limited employment opportunities and economic factors motivate people to look for opportunities to find work abroad. Indonesians feel that working abroad is expected to improve their economic and social conditions. This research uses the Empirical judicial method, which can also be called field research. Data collection techniques in this study used direct interviews, literature studies, and descriptive qualitative data processing technique. The results showed that the provision of protection to Indonesian Migrant Workers After placement, protection is provided to their families in the form of empowerment programs and new entrepreneurial assistance for former migrant workers and their families. Fulfillment of rights for former Indonesian migrant workers in the form of family rights and the rights of former migrant workers Rights for former migrant workers in the form of remittance management, which is useful for improving welfare and rights.